2011
DOI: 10.1073/pnas.1102309108
|View full text |Cite
|
Sign up to set email alerts
|

The p53 inhibitors MDM2/MDMX complex is required for control of p53 activity in vivo

Abstract: There are currently two distinct models proposed to explain why both MDM2 and MDMX are required in p53 control, with a key difference centered on whether these two p53 inhibitors work together or independently. To test these two competing models, we generated knockin mice expressing a point mutation MDMX mutant (C462A) that is defective in MDM2 binding. This approach allowed a targeted disassociation of the MDM2/MDMX heterocomplex without affecting the ability of MDMX to bind to p53, and while leaving the MDM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(184 citation statements)
references
References 24 publications
7
176
0
1
Order By: Relevance
“…Consistent with this prediction, two recent reports from Yuan's and Lozano's groups demonstrated that knock-in of MdmX RING domain mutants either as point mutant MdmxC462A or as RING domain deletion in mice caused a p53-dependent embryonic lethal phenotype. 81,82 In both cases, the time point of embryonic lethality was embryonic day 9.5, which is similar to knockout of the whole gene of MdmX. 57 These results suggest that the RING domain of MdmX carries the whole function of MdmX protein in p53 inhibition during development.…”
Section: The Essential Role Of Ring Domain Of Mdmx In P53 Degradationsupporting
confidence: 48%
See 1 more Smart Citation
“…Consistent with this prediction, two recent reports from Yuan's and Lozano's groups demonstrated that knock-in of MdmX RING domain mutants either as point mutant MdmxC462A or as RING domain deletion in mice caused a p53-dependent embryonic lethal phenotype. 81,82 In both cases, the time point of embryonic lethality was embryonic day 9.5, which is similar to knockout of the whole gene of MdmX. 57 These results suggest that the RING domain of MdmX carries the whole function of MdmX protein in p53 inhibition during development.…”
Section: The Essential Role Of Ring Domain Of Mdmx In P53 Degradationsupporting
confidence: 48%
“…Knockout of Mdm2 and knock-in of Mdm2 RING mutant kill the embryos at the earlier developmental stage of Day 5.5-7.5, 61,83,84 while knockout of MdmX or knock-in of MdmX RING mutant kill the embryos at the later stage of day 9.5. 57,81,82 These observations imply that Mdm2-mediated p53 inhibition at an earlier developmental stage depends on its RING domain but does not need MdmX. The possible mechanisms underlying this stage of p53 inhibition might be (1) Mdm2-mediated monoubiquitination drives p53 nuclear export which is sufficient for inactivation of p53 nuclear activity or (2) on top of nuclear exporting of p53 by Mdm2-catalyzed monoubiquitination, other E3 ligases or E4 factors can complete the ubiquitin-dependent degradation process in the cytoplasm.…”
Section: The P53 E3 Ligase: Mdm2/mdmx and Beyondmentioning
confidence: 99%
“…Mutation of the conserved cysteine residue in the MdmX RING domain, C462A, disrupts dimerization with Mdm2 and allows for p53 activation, leading to embryonic lethality by day 9.5 (17). Notably, in the …”
Section: Discussionmentioning
confidence: 99%
“…The rescue of Mdm4 knockout and Mdm4 RING domain mutant mice by p53 deficiency concluded that Mdm4 has a non-overlapping function of Mdm4 with Mdm2. 12,13,19 However, this conclusion is difficult to reconcile with the finding that an Mdm2 transgene containing Mdm2 gene and its native promotor can completely rescue Mdm4-deficiency-induced p53-dependent lethality, leading to a conclusion that Mdm2 and Mdm4 are functionally overlapping in development. 28 Based on our biochemical model, it is higly likely that the Mdm2 splice isoforms expressed from the Mdm2 transgene, rather than the overexpression of full-length Mdm2 per se, may have compensated for the loss of Mdm4 as a RING-domain stimulater of full length Mdm2 activity to fully suppress p53 during development.…”
Section: Mdm2 Isoforms Are Super Active E3 Ligase For Ubiquitination mentioning
confidence: 99%
“…10 Mouse genetics studies indicated that RING-RING interaction of Mdm2-Mdm4 domain is essential for restricting p53 activity during embryonic development, since mutation of either Mdm2 or Mdm4 RING domain causes p53-dependent embryonic lethality. [11][12][13] Mdm2 alternative splice isoforms were reported years ago. 14 Two major splice isoforms Mdm2-A and Mdm2-B (referred thereafter as Mdm2-A/B) do not bind to p53 and induce p53-independent cell growth in vivo and tumorigenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%